2013
DOI: 10.1364/ao.52.000879
|View full text |Cite|
|
Sign up to set email alerts
|

Analyzing the effects of particle size on remotely sensed spectra: a study on optical properties and spectral similarity scale of suspended particulate matters in water

Abstract: Particle size is an important factor for determining the concentration of suspended particle matter (SPM) in water using optical remotely sensed data. We collected reflectance spectra of five SPM samples with different particle sizes in a controlled laboratory experiment using a spectroradiometer. The theoretical relationship between particle size distributions and backscattering coefficient was deduced based on a spectral reflectance model. The backscattering coefficient of the complete SPM sample can be comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…This suggests that the suspended sediment particle properties such as size distributions, compositions, and textures might be different for the Yellow River and Yangtze River. In fact, a recent study from Lake Taihu shows that particle size distribution plays an important role for the measured r wN (l) spectra (Lu et al 2013). Zhang et al (2008) also reported that the compositions of river sediments from Yellow River and Yangtze River are different.…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that the suspended sediment particle properties such as size distributions, compositions, and textures might be different for the Yellow River and Yangtze River. In fact, a recent study from Lake Taihu shows that particle size distribution plays an important role for the measured r wN (l) spectra (Lu et al 2013). Zhang et al (2008) also reported that the compositions of river sediments from Yellow River and Yangtze River are different.…”
Section: Methodsmentioning
confidence: 99%
“…Between 1983 and 2009 accumulation of sediments drop from 158 × 10 6 m 3 to 6.1 × 10 6 m 3 yr -1 (Nooren et al, 2017). Nowadays, the algorithms and models developed to calculate SSC take into account changes in the spectral response of the sediments, as well as atmospheric variables (Lu et al, 2013;Qu et al, 2016;Zhang et al, 2015). In the dispersion diagram the relationship between both variables is low due the high atmospheric interference between the satellite and water surface; additionally, water vapor and aerosols are present, which causes the sensor not to detect the total reflectance of the sediments.…”
Section: Discussionmentioning
confidence: 99%
“…Turbidity in bentonite clay and black cotton soil was linearly related to reflectance, whereas the turbidity of kaoline and grey soil is curvilinearly related to reflectance (Bhargava and Mariam 1990). A number of studies have investigated the effect of particle size on the remote sensing of sediment concentration (Lu et al 2013;Tilstone et al 2012;Astoreca et al 2012;Bowers et al 2009), but few works have been done on the effect of the distribution of particle composition along a river. Sediment variability is significant in river waters because of the high sediment variety originating from the runoff from vast agricultural areas.…”
Section: Introductionmentioning
confidence: 99%